Stay Sane Inside Insanity: The Occult Classical and The Propagation of Hedonistic Insanity in The Rocky Horror Picture Show - Čop, Noemi (Music with a Message: Words, Music and Propaganda 2, 2025)
The LGBTQ+ community’s struggle for equality is a tale as old as time. For example, in the early 1970s they were oppressed, beaten, and marginalised. They were even perceived as aliens. Richard O’Brien gave the “aliens” a voice and celebrated their “alienness” in the script for the musical The Rocky Horror Show, which became popular enough to be made into a movie, The Rocky Horror Picture Show (1975). As the film became a cult classic, it opened a door for a wider audience to become acquainted with the LGBTQ+ community. Though they are shown as a group of immoral hedonistic aliens from the planet Transsexual, in the galaxy Transylvania, their effect on the everyday human is undeniable. In this chapter, I will discuss how the main antagonist’s similarity to the god Dionysus, along with the film’s allusions to Greek mythology, help propagate “Trans-bacchanals” and normalise otherness.